Double Trouble - Radiological Abnormality - Sohail Mohammed Balbatti (Al Ameen Journal of Medical Sciences)
Double aortic arch (DAA) is a rare congenital anomaly of the aortic arch system, representing the most common vascular ring malformation. Axial and Coronal CT aortogram images of our patient demonstrate a prominent right arch and a smaller left arch forming a complete vascular ring, causing trachea-esophageal compression. This condition can lead to significant respiratory and digestive symptoms due to the encirclement of the trachea and esophagus by connected segments of the aortic arch.